SOLUTION
Given the question in the image, the following are the solution steps to answer the question.
STEP 1: Write the given data
![\begin{gathered} \text{directrix}=x=-4 \\ \text{Focus:}(2,4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ume41deplayhn2elun6emxmh00yiqclvti.png)
STEP 2: Write the equation of a parabola
![\begin{gathered} \text{The equation is given as:} \\ x=(1)/(4(f-h))(y-k)^2+h\text{ where} \\ (h,k)\text{ is the vertex} \\ (f,k)is\text{ the focus} \\ \text{Thus,} \\ f=2,k=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s6kz4nqbqylf6esqrxsid1vto45xou2d3w.png)
STEP 3: Get the value of h
The distance from the focus to the vertex is equal to the distance from the vertex to the directrix. Therefore:
![\begin{gathered} f-h=h-(-4) \\ By\text{ substitution}, \\ 2-h=h+4 \\ 2-4=h+h \\ -2=2h \\ h=-(2)/(2)=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/us5mhsrzqc0rd2bhxko7fm05o1yyao6l1p.png)
STEP 4: Get the standard form of equation
Hence, the standard form becomes:
![\begin{gathered} \text{The standard form is given as:} \\ x=(y^2)/(12)-(2y)/(3)+(1)/(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rbu3er3zl66m178gbada2e82i7djvmt5w8.png)